Cadomian (Ediacaran-Cambrian) arc magmatism in the Bitlis Massif, SE Turkey: Magmatism along the developing northern margin of Gondwana - Ustaomer, P. Ayda; Ustaomer, Timur; Collins, Alan S.; Robertson, Alastair H. F. (ELSEVIER, 2009)
Small granitic plutons and associated granitic dykes that intrude the pre-Devonian basement of the Bitlis Massif were previously inferred to have a broadly Late Palaeozoic crystallisation age related to the Hercynian orogeny; this was tested during this work. The brittle-ductile-deformed Mutki granite pluton and nearby granitic dykes comprise mainly quartz, alkali feldspar, plagioclase, subordinate biotite, muscovite and rare amphibole. Based on the results of whole-rock major-element and trace-element analysis, the Mutki pluton and associated dykes are inferred to have crystallised from metaluminous, to peraluminous subduction influenced I-type melts. Sm-Nd isotope systematics indicate melting of a mantle source (of notional 1.3 Ga age), with increasing amounts of crustal contamination through time. U/Pb zircon dating of the Mutki granite and a nearby granitic dyke by laser inductively coupled plasma mass spectrometry (LA-ICP-MS) yielded U-238/Pb-206 crystallisation ages of 545.5 +/- 6.1 Ma and 531.4 +/- 3.6 Ma, respectively (Ediacaran-Early Cambrian). This shows for the first time that the regionally extensive Bitlis Massif was affected by Cadomian arc-type magmatism. The Ediacaran-Early Cambrian granitic rocks of the Bitlis Massif can be compared with similar-aged metagranitic and metavolcanic rocks within basement units exposed in the Tauride-Anatolide Platform (Menderes-Taurus Block) in western Anatolia and also in NW Turkey. Similar-aged rocks are also exposed in the basement of Iran. All of these magmatic units and their host rocks are interpreted as fragments of a Cadomian active margin bordering the northern margin of Gondwana after its final amalgamation. Formation of the Bitlis Massif granites and contemporaneous granitic units elsewhere in Turkey as fragments of an Andean-type margin adjacent to the Arabian-Nubian Shield is favoured over an alternative explanation as exotic terranes transported >2000 km eastwards from a Cadomian active margin near West Africa-Amazonia (now NW Africa). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: LA-ICP-MS U/Pb zircon dating; Ediacaran-Cambrian magmatism; Granite; Bitlis Massif; Turkey; Northern margin of Gondwana; SOUTHERN MENDERES MASSIF; U-PB GEOCHRONOLOGY; BOLU MASSIF; GEOLOGICAL EVOLUTION; WESTERN TAURIDES; SANDIKLI AREA; NW TURKEY; ROCKS; GRANITOIDS; PETROGENESIS; Geochemistry & Geophysics